Arthropod moulting hormones (ecdysteroids) are present in the blood of insectivorous bats. (26th January 2022) - Hornok, Sándor; Berkecz, Róbert; Sós, Endre; Sándor, Attila D.; Körmöczi, Tímea; Solymosi, Norbert; Kontschán, Jenő; Hunyadi, Attila
Abstract: Ecdysteroids are steroid hormones involved in moulting and development of arthropods. Blood samples of 32 individual bats of eight insectivorous species were analysed for the presence of ecdysteroids, using liquid chromatography and mass spectrometry. Nine ecdysteroids were detected. The spectrum of these ecdysteroids was similar in bat species which take their preferred food items from the same insect order. The spectrum of blood‐borne ecdysteroids was broader in the autumn than in the summer, and higher concentrations of 20‐hydroxyecdysone (the most common ecdysteroid) occurred in samples from large bat species than from small ones. Ecdysteroids may have anabolic effects on insectivorous bats and may also affect their blood‐feeding arthropod parasites. Abstract : This study provides evidence for the presence of insect moulting hormones (so‐called ecdysteroids) in the blood of echolocating bats. These blood‐borne steroid hormones in bats most likely originate from their food items, because all evaluated species are insectivorous.